Zero distribution of sequences of classical orthogonal polynomials - Plamen Simeonov (Abstract and Applied Analysis)
We obtain the zero distribution of sequences of classical orthogonal polynomials associated with Jacobi, Laguerre, and Hermite weights. We show that the limit measure is the extremal measure associated with the corresponding weight.